A critical analysis of the prohibition of sodomy and same sex marriages in Zimbabwe: a human rights perspective - Madzikatire, Victor Gwinyai (Midlands State University, 2014)
A same-sex marriage is ‘the ceremonial union of two people of the same sex. It is a marriage or marriage like relationship between two women or two men’. This is a highly contentious concept. It is defined primarily, by the sexual orientation of the individuals. Sexual orientation refers to the direction of an individual sexual and emotional attraction, whether to individuals of a different sex (heterosexual), same sex (homosexual) or both sexes (bisexual.) Consequently, sexual orientation has been protected in other jurisdictions as a ground of non- discrimination. This was due to the realization that sexual orientation can be used as a ground of discrimination. This results in the creation of a sexual minority which is united by their close connection with the right holder’s minority sexual orientation. Therefore, this has culminated in the recognition of the rights-related claims of people whose sexual and gender identity challenge social and cultural prescriptions as a distinct branch of human rights law. This is due to an appreciation of the fact that human rights are indivisible, interrelated and interdependent through the equal and non-discriminatory application of the law.